Estimation of Willingness-to-Pay Theory, Measurement, Application - Breidert, Christoph; SpringerLink (Online service) (Wiesbaden : DUV, 2006)
To determine the willingness-to-pay (WTP) for products and/or services from a customer perspective is crucial for modern approaches to pricing. With the Price Estimation scene (PE scene) Christoph Breidert introduces a new method to estimate WTP. It works as an additional interview scene appended to conjoint analysis and offers the respondents a dynamically generated sequence of product choices with assigned prices. The customers indicate whether they would actually purchase the presented product profiles. The PE scene is tested in an empirical investigation in which the WTP of the customers of the Nokia online shop in Germany was estimated for different product bundles.
Pricing in the Marketing Mix -- Willingness-to-Pay (WTP) in Marketing -- Measuring Willingness-to-Pay -- Conjoint Analysis -- Conjoint Analysis in Pricing Studies -- Price Estimation Scene (PE Scene) -- Empirical Investigation: Nokia study -- Summary and Main Findings.
Keywords: Business; Marketing; Business and Management; Marketing; Electronic books